Evaluation of wind park tax incentives in Colombia by means of real options - Miguel Jiménez-Gomez; Natalia Acevedo-Prins (Institute of Advanced Engineering and Science, 2020)
The objective of this study is to assess tax incentives in Colombia to foster investment in wind parks. Fiscal incentives seek to diversify energy consumption with non-conventional renewable energy sources, since power is mostly generated by hydraulic force and since its price is impacted during dry seasons. The price of energy is modeled according to a regression toward the mean. This stochastic process was chosen because during droughts in Colombia there are price increases, which then return to their average value. This is an upward and downward spike behavior, as well as a regression toward the mean. Given price uncertainty and its impact on cashflow, wind parks were valued with real options to flatten the reversal for five years. The real option of flattening as an American call option was considered. Results show that, according to traditional valuation methods, wind parks in Colombia are not profitable even with tax incentives. However, according to the real options method, tax incentives do make these projects economically viable.